The mediating role of employee engagement in the relationship between human resource management practices and employee turnover intention - Shalini, Youvarajan (2021)
This research aimed to analyse the mediating role of employee engagement in the relationship between human resource management practices and employee turnover intention. Questionnaires were distributed in 5 different zone areas in Penang, mainly focusing on manufacturing industrial employees. There were a total of 155 respondents who represented the organizations in line of answering the surveys. Employees were asked about their level of work engagement and performance. The direct relationship between human resource management practices and employee turnover intention was not statistically supported. However, support was found for employee engagement as a mediator in the relationship between human resource management practices and employee turnover intention. This suggests that several human resource management practices highlighted in this research include internal career ladder, training, performance appraisal, and employee voice & participation, which impact employee turnover intention. The limitation of research and future research recommendations were discussed and highlighted that organizations should focus more on human resource management Practices and improve existing employee engagements.